Effects of canarium fruit (Canarium odontophyllum) oil as a dietary lipid source for juvenile mahseer (Tor tambroides) performance - Bami, Mahkameh Lashkarizadeh (Elsevier, 2017)
Canarium is among the riverine fruits that are commonly found in the natural diet of Malaysian mahseer, Tor tambroides. The fruit contains a high percentage of lipids. This study was conducted to investigate the effects of canarium crude oil on the growth performance, body composition and fatty acid profile of juvenile T. tambroides. Five isonitrogenous (40% crude protein) diets containing varying canarium oil levels (0, 1.25, 2.5, 3.75 and 5%) were prepared. Crude palm oil (CPO) was used as the control. The juveniles (2.08 ± 0.10 g) were given the test diets for 12 weeks in triplicate groups. Diets containing canarium oil were found to be less accepted by the fish which led to a significantly lower (P < 0.05) daily feed intake than diet including 0% canarium oil. Juveniles fed on 1.25–5% canarium oil also showed significantly lower (P < 0.05) weight gain, specific growth rate, and protein efficiency ratio than those fed 0% canarium oil. However, the canarium oil level did not have any significant effect (P > 0.05) on survival and lean portion of juvenile T. tambroides. The fish fed canarium oil-free diet also had better tissue fatty acid profile (especially n-3 and n-6 PUFA) as well as better protein, lipid and energy retention than those fed diets including canarium oil. From the results, canarium oil extracted from the whole fruit was not recommended as a dietary lipid source for T. tambroides. Moreover, juveniles fed on 0% canarium oil (5% CPO) utilized dietary saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) more efficiently for their energy requirement than fish given canarium oil.